2016
DOI: 10.5194/tc-10-2057-2016
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of solute locations in laboratory ice samples

Abstract: Abstract. Many important chemical reactions occur in polar snow, where solutes may be present in several reservoirs, including at the air–ice interface and in liquid-like regions within the ice matrix. Some recent laboratory studies suggest chemical reaction rates may differ in these two reservoirs. While investigations have examined where solutes are found in natural snow and ice, few studies have examined either solute locations in laboratory samples or the possible factors controlling solute segregation. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…ESEMs are therefore becoming increasingly popular within research into pure ice (Nair et al, 2018;Magee et al, 2014;Chen et al, 2017) and ice-impurity interactions under static and dynamically changing conditions (Krausko et al, 2014;Yang et al, 2017). While electron microscopy visualizes the sample surface in detail, microcomputed tomography has been recently applied to investigate solute locations in the frozen bulk (Hullar and Anastasio, 2016). Using this technique, the authors were able to visualize the locations of solutes (CsCl or rose bengal), gas, and ice in 3-D.…”
Section: L' Vetráková Et Al: a Study Of The Freezing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ESEMs are therefore becoming increasingly popular within research into pure ice (Nair et al, 2018;Magee et al, 2014;Chen et al, 2017) and ice-impurity interactions under static and dynamically changing conditions (Krausko et al, 2014;Yang et al, 2017). While electron microscopy visualizes the sample surface in detail, microcomputed tomography has been recently applied to investigate solute locations in the frozen bulk (Hullar and Anastasio, 2016). Using this technique, the authors were able to visualize the locations of solutes (CsCl or rose bengal), gas, and ice in 3-D.…”
Section: L' Vetráková Et Al: a Study Of The Freezing Methodsmentioning
confidence: 99%
“…The impurities' locations were most often deduced from the sample preparation methods; for example, freezing an aqueous solution involved the precondition of placing the impurities inside the ice matrix. Subsequent breaking of the ice into small pieces was proposed to bring the impurities to the ice surface (Kahan et al, 2010); this assumption was recently questioned (Hullar et al, 2018). Other studies suggested that freezing an aqueous solution places the impurities prevalently inside the ice interior, whereas deposition of the organics from the vapor phase accommodates them on the ice surface (Ondrušková et al, 2018;Vetráková et al, 2017;Krausko et al, 2015a, b;Kania et al, 2014;Heger et al, 2011;Hullar et al, 2018;Bartels-Rausch et al, 2013).…”
Section: L' Vetráková Et Al: a Study Of The Freezing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These brine pools occasionally appear at the locations of caverns formed by bubbles, thus 445 delineating the grain boundary, which would otherwise be difficult to observe. 446 The fact that ice is a very dynamic medium allowing reconstitution at sub-zero temperatures was 454 previously evidenced using, for example, time-lapse X-ray tomography; up to 60 % of the total ice mass 455 recrystallized during 12 hours at -15 °C (Pinzer and Schneebeli, 2009;Hullar and Anastasio, 2016). Our 456 research team is not the first one to have observed disjoint behavior of the ice surface in relation to 457 the underlying ice crystals; fresh ice growing in steps of 100 -4,000 nm to traverse the ice grains 458 regardless of the boundaries was already noticed for planar ice growth (Ketcham and Hobbs, 1968).…”
Section: Formation Of the Humps 411mentioning
confidence: 96%
“…The results have 28 straightforward implications for artificially prepared and naturally occurring salty ices. probably influences the compounds' reactivity as their availability to incoming light radiation and/or 39 gaseous reactants substantially differs depending on whether the impurities are located on the ice 40 surface or buried in the frozen bulk (Hullar and Anastasio, 2016). However, the information combining 41 the reactivity of compounds with their locations is essentially missing.…”
mentioning
confidence: 99%